Local connections among excitatory neurons underlie characteristics of enriched environment exposure-induced neuronal response modulation in layers 2/3 of the mouse V1 - Wagatsuma, Nobuhiko; Terada, Yuka; Okuno, Hiroyuki; Ageta-Ishihara, Natsumi (Frontiers in Systems Neuroscience, 2025)
Environmental enrichment, an enhancement in the breeding environment of laboratory animals, enhance development of the cortical circuit and suppresses brain dysfunction. We quantitatively investigated the influences of enriched environment (EE) exposure, on responses in layers 2/3 (L2/3) of the primary visual area (V1) of mice. EE modifies visual cortex plasticity by inducing immediate early genes. To detect this, we performed immunostaining for the immediate early gene product c-Fos. EE exposure significantly increased the number of neurons with high c-Fos fluorescence intensity compared with those of mice under standard housing (SH). In contrast, there was no significant difference in the number of neurons exhibiting low c-Fos intensity between the SH and EE exposure groups. To further investigate the mechanism of modulation by EE exposure, we developed a microcircuit model with a biologically plausible L2/3 of V1 that combined excitatory pyramidal (Pyr) neurons and three inhibitory interneuron subclasses. In the model, synaptic strengths between Pyr neurons were determined according to a log-normal distribution. Model simulations with various inputs mimicking physiological conditions for SH and EE exposure quantitatively reproduced the experimentally observed activity modulation induced by EE exposure. These results suggested that synaptic connections among Pyr neurons obeying a log-normal distribution underlie the characteristic EE-exposure-induced modulation of L2/3 in V1.